"Have This Mind in You" A Study of the Relationship between Pauline Christology and the Tathāgatagarbha Tradition of Mahayana Buddhism - Worssam, Nicholas Alan (2020)
This study of the interrelationships between the doctrine of Christ in the New Testament writings of St. Paul and the Buddha-nature (Sanskrit: Tathāgatagarbha) tradition of Mahayana Buddhism attempts to bring out some areas of potentially fruitful dialogue. In particular, three strands of parallel use of imagery emerge: the Buddha-nature is referred to as the "Truth-body" of the Buddha (dharmakāya) "when not free from the store of defilement." As such, the Buddha-nature is seen as the ultimate truth/way of all things, yet hidden by, for example, greed, hatred, and delusion. It is the disguised support of saṃsāra and nirvāṇa, the cyclical world of appearances and the ultimate release from all delusion. This is compared with Christ as the Wisdom of God holding all things in being yet "secret and hidden," ceaselessly active in the world yet undefiled., Secondly, according to some Mahayana texts, the Buddha-nature is the "true self" and is identified with the radiant substratum-consciousness or Mind. This is compared with the "new self" of the Pauline writings, identified as the "mind of Christ," which is radiant with the glory of God., Thirdly, as the womb of Buddhahood, the Buddha-nature is full of the manifold qualities of the Buddha, showing the potential of all beings to manifest these qualities. Likewise, the "fullness of God" dwells in Christ who draws believers into his own fullness and is thus the hope of glory for all who realize their unity in the body of Christ.
Keywords: Buddha-nature; Christ; Christology; Tathāgatagarbha; Defilement; dharmakāya; Emptiness; fulness; Mind; Self